(untitled) (Global Journal of Human-Social Science, 2021)
Maritime transport remains backbone of globalized trade and manufacturing supply chain, as more than 80% of world merchandise trade by volume is carried by sea. Maritime transport in Kenya takes care of 90% of Kenya’s international trade by volume. The objective of this study was to establish effect of labor productivity on maritime sector performance in enhancing economic growth in Kenya. Target population was Kenya Ports Authority and Kenya Ferry Services while Kenya Maritime Authority coordinated implementation of policies relating to maritime affairs. The study was guided by the Solow growth model and the production theory. The study adopted explanatory research design employing panel data using data on annual basis over the period 2000-2019. Simple Linear Regression and GMM Models were utilized. Using STATA 13.0 and applying Simple Regression model, results indicated that coefficient of foreign exchange rate was 3.5694 which was positive and significant at 5% level, , implying every one percent increase in coefficient of foreign exchange rate, output increased by 3.5694%.